Fuzzy logic based convective cloud detection from the Kalpana data - Ravi Kumar, B; Anuradha, B (International Journal of Engineering and Technology, 2018)
The cloud classification and analysis of the distinctive convective clouds from the satellite data have been mobilized using many traditional classification methods in atmospheric models for foreseen the natural hazards. In this paper one promising method makes use of fuzzy logic to perceive the convective clouds with strong triangular and trapezoidal membership functions. Convective clouds extracted from satellite images are compared with INSAT Multispectral Rainfall Algorithm (IMSRA).The development of the fuzzy logic rule based expert system with Kalpana satellite spectral data consist of advanced very high resolution (AVHRR) channels, which include Water vapour, infrared windows. In this proposed method shows that the fuzzy logic method offers greater correct results than conventional algorithms to identify the convective clouds.Â Â Â